Influência de diferentes níveis de vitamina C na ração sobre parâmetros hematológicos de alevinos de Piaractus mesopotamicus Holmberg (Osteichthyes, Characidae) - Martins, Maurício Laterça [UNESP] (1995)
Haematological changes in ascorbic acid deficient fishes, observed by some authors, awoked the interest in the haematological response of pacu, Piaractus mesopotamicus. The present work studied the influence of different levels of ascorbic acid (vitamin C) in the ration on the haematological parameters of pacu. Fishes at the beginning of the experiment, presented average body weight 8.64±1.62g and 6.15±0.33cm standard length, were fed with diets containing 0. 50, 100 and 200mg ascorbic acid/kg dry ration. The present work was developed for a period of 24 weeks at the Fish Nutrition Laboratory of Aquaculture Center of Universidade Estadual Paulista (Unesp), Jaboticabal (São Paulo). The fishes were distributed by the completely randomized design in 20 aquaria of 100 liters capacity with six animals in each and five fold treatment. Condutivity, alcalinity. pH and oxigen were measured weekly and temperature daily. The blood colect was done in 60 anesthetized fishes with 50mg MS-222/1. The results suggests that 50mg ascorbic acid/kg dry ration improved the mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration and decreased haematocril in unsupplemented fishes, although not differing significantly (P>0.05). The erytrocyte diameter indicated the presence of macrocytic cells in unsupplemented fishes (P<0.05) and the regression analysis showed too reduced neutrophils in unsupplemenled ones, 50mg ascorbic acid/kg dry ration supplementation was enough to development and haematological responses. Furthtermore, the optimum level to the growth is 139mg vitamin C/kg dry ration (P<0.05).